Effect of Learning Motivation, Family Factor, School Factor, and Community Factor on Student Learning Outcomes on Productive Subjects - Oktaviani Pratiwi Wijaya; Imam Bukhori (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
This study aims to determine: (1) conditions of learning motivation, family factors, school factors, community factors and learning outcomes; (2) the influence of learning motivation on learning outcomes; (3) the influence of family factors on learning outcomes; (4) the influence of school factors on learning outcomes; (5) the influence of community factors on learning outcomes; (6) the influence of learning motivation, family factors, school factors and community factors on learning outcomes. The population in this study is all students of class X Class Office Administration Study Program as many as 109 students, the sample used as many as 86 students using proportional random sampling technique. Data analysis techniques used are descriptive statistics and multiple linear regression analysis. The results showed that: (1) learning motivation can be classified well, the family factor can be classified very well, school factor can be classified well, society factor can be classified well; (2) learning motivation has no significant effect on learning outcomes; (3) family factors partially have a positive and significant effect on learning outcomes; (4) school factors partially have a positive and significant impact on learning outcomes; (5) community factors partially have a positive and significant impact on learning outcomes; (6) learning motivation, family factor, school factor and community factor simultaneously have a positive and significant impact on learning outcomes.